Simulação CFD de transferência de calor conjugada convecção natural-condução em uma cavidade semicircular contendo um fluido com geração de calor interna - Arruda, Wallthynay Ferreira de (2019)
Following the Fukushima accident, there is clear progress in studies and researches involving safety in nuclear power plants to prevent accidents with total or partial degradation of the reactor core, known as a severe accident. In order to ensure the physical integrity of the reactor pressure vessel in the event of a severe accident, the aim of this dissertation is to investigate the conjugate heat transfer in a fluid with internal heat generation in a semicircular cavity with heat conduction in the wall and quantify the effects of thickness (b) on diameter (D) and a reason of solid and fluid thermal conductivity (K). Isothermal conduction of the boundary is imposed on the outer surface of the cavity wall. For comparison, unconjugated natural convection in the semicircular cavity is also simulated, with the isothermal boundary condition imposed on the cavity’s inner surface. Two-dimensional computer simulations were performed using the ANSYS FLUENT v.18.2 commercial software for laminar flow. With Prandtl numbers equal to 0.032, 0.71 and 7.01 in a semicircular cavity with and without thick wall, thus making a comparison and analyzing its importance to the problem. The results for the unconjugated case showed that the mean numbers of Nusselt on the upper surface of the semicircular cavity were in agreement with the correlations of Mayinger et al (1976) and Kulacki and Emara (1975). The mean number of Nusselt on the lower surface of the semicircular cavity was in excellent agreement with Mayinger et al. (1976). For the conjugated case, the average numbers of Nusselt were in line with the study by Liaqat and Baytas (2001) in the range of Ra = 10 6 a Ra = 10 10.